2017
DOI: 10.2174/1567201813666161006114448
|View full text |Cite
|
Sign up to set email alerts
|

The Efficiency of Tat Cell Penetrating Peptide for Intracellular Uptake of HIV-1 Nef Expressed in E. coli and Mammalian Cell

Abstract: This data indicated that the Tat gene sequence could also increase the transfection of Nef gene in vitro. Generally, the Tat-Nef interaction led to enhance further gene expression and also protein delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…GALA, KALA, and histidine-rich peptides) could enhance transfection efficiency along with poly-lysine/DNA complexes [100]. Another report indicated that the Tat peptide increased in vitro transfection of HIV-1 Nef gene (as Tat-Nef fusion DNA) and subsequently its expression in mammalian cells [208]. Hyndman et al demonstrated that mixing the Tat with liposomes containing DOTAP/Lipofectin and DNA led to generate the complexes that significantly increased in vitro transfection [209].…”
Section: Nucleic Acid Deliverymentioning
confidence: 99%
“…GALA, KALA, and histidine-rich peptides) could enhance transfection efficiency along with poly-lysine/DNA complexes [100]. Another report indicated that the Tat peptide increased in vitro transfection of HIV-1 Nef gene (as Tat-Nef fusion DNA) and subsequently its expression in mammalian cells [208]. Hyndman et al demonstrated that mixing the Tat with liposomes containing DOTAP/Lipofectin and DNA led to generate the complexes that significantly increased in vitro transfection [209].…”
Section: Nucleic Acid Deliverymentioning
confidence: 99%
“…Examples include the first discovered membrane penetrating peptide, Tat, a typical arginine-rich membrane penetrating peptide. Human immunodeficiency virus type 1 (HIV-1) Tat protein, secreted from infected cells, can deliver several proteins, including ovalbumin, β-galactosidase, and horseradish peroxidase into cells [ 20 , 21 , 22 ]. The primary domain in Tat protein responsible for crossing the plasma membrane, the protein transduction domain (PTD), is rich in arginine and lysine residues.…”
Section: Introductionmentioning
confidence: 99%
“…In this line, the formation of Pep-1 and/ or Cady-2/ Nef protein complexes as discrete nanoparticles was confirmed by SEM analysis with an average size of ~150-250 nm [52]. Furthermore, the Pep-1 and Cady-2 delivery systems could increase the potency of Tat CPP conjugated to Nef (Tat-Nef) for cell penetration [52, 53]. Analysis of the immune responses demonstrated that the Tat-Nef + Gp96 DNA prime/Tat-Nef protein+Cady-2 boost regimen significantly enhanced the Nef-specific T cell responses [52].…”
Section: Discussionmentioning
confidence: 99%